Approaches to plant evolutionary ecology - Cheplick, G. P. (Gregory Paul), 1957- (Oxford University Press, 2015)
Plant evolutionary ecology is a rapidly growing discipline which emphasizes that populations adapt and evolve not in isolation, but in relation to other species and abiotic environmental features such as climate. Although it departs from traditional evolutionary and ecological fields of study, the field is connected to branches of ecology, genetics, botany, conservation, and to a number of other fields of applied science, primarily through shared concepts and techniques. However, most books regarding evolutionary ecology focus on animals, creating a substantial need for scholarly literature with an emphasis on plants. Approaches to Plant Evolutionary Ecology is the first book to specifically explore the evolutionary characteristics of plants, filling the aforementioned gap in the literature on evolutionary ecology. Renowned plant ecologist Gregory P. Cheplick summarizes and synthesizes much of the primary literature regarding evolutionary ecology, providing a historical context for the study of plant populations from an evolutionary perspective. The book also provides summaries of both traditional (common gardens, reciprocal transplants) and modern (molecular genetic) approaches used to address questions about plant adaptation to a diverse group of abiotic and biotic factors. Cheplick provides a rigorously-written introduction to the rapidly growing field of plant evolutionary ecology that will appeal to undergraduate and graduate students with an interest in ecology and evolution, as well as educators who are teaching courses on related topics.